Prognostic value of neutrophil-to-lymphocyte ratio in patients undergoing curative surgical resection for hepatocellular carcinoma - Gokhan Saritas, Ahmet; Ulku, Abdullah; Topal, Ugur; Dalci, Kubilay; Cem Eray, Ismail; Tolga Akcam, Atilgan (Annals of Medical Research, 2021)
Aim: the purpose of this study is to determine the prognostic value of the preoperative Neutrophil-to-Lymphocyte ratio (NLR) in patients who underwent curative surgical treatment for hepatocellular carcinoma (HCC). Materials and Methods: Patients who underwent curative resection for HCC between 2004 and 2015 were included in the study. Patients were divided into two groups based on the cut-off value: Group 1 (NLR low) and Group 2 (NLR elevated). Demographics and clinical characteristics, tumor characteristics, and mean survival of patients were compared between the groups.Results: 41 patients were included in our study and Group 1 (NLR low) consisted of (n:11) patients; Group 2 (NLR elevated) consisted of (n:30) patients based on a cut-off value of 2.43. The number of males was higher in both groups (90.9% vs 90%, p:0.712). The Child-Plug class A was the most common one in both groups (81.8%vs76.7%, p:0.680). HBV infection was the most common etiological cause (81.8% vs 53.3%, p:0.344). Lesions were predominantly located in the right lobe (63.6% vs 66.7%, p:0.568). The total tumor diameter was similar (6.56 cm vs 8.69 cm, p:0.258). In the multivariate analysis for survival, tumor diameter greater than 5 cm (HR 1.412 95% - Cl0.345-5.780, p:0.018) and NLR higher than 2.43 (HR 0.100 95% -Cl 0.011-0.882, p:0.038) were independent risk factors. Overall survival time was found to be lower in Group 2 compared to Group 1 (171 vs 106 months p:0.033). Disease-free survival rates were similar in the groups (37 vs 43 months, p:0.485).Conclusion: Although the elevated NLR level was found to be a risk factor for decreased overall survival in our study, this was not related to clinicopathological variables.